The anthrax vaccine : is it safe? does it work? (National Academy Press, 2002)
The National Academy Press presents the full text of the book "The Anthrax Vaccine: Is it Safe? Does it Work?", by the Committee to Assess the Safety and Efficacy of the Anthrax Vaccine, Institute of Medicine. The book reports the study's conclusion that the vaccine is acceptably safe and effective in protecting humans against anthrax. The book also includes a description of advances needed in main areas: improving the way the vaccine is now used, expanding surveillance efforts to detect side effects from its use, and developing a better vaccine.